Comparative study of sperms motility analysis with CASA by using leja and microscope slide - Dian Ratnawati; Muchamad Luthfi (Faculty of Animal Science, Universitas Brawijaya, 2020)
The aim of this study was to compare the assessment of spermatozoa motility by using leja and microscope slide (MS). Fresh semen of four Ongole crossbred (PO) bulls were collected by using an artificial vagina. The semen with 70% sperms motility was diluted into into 30 million/ml concentration and assessed for its motility by using CASA (SCA 5.2 Microptic). The measured parameters in this study were sperms motility, progressive sperm motility, curve linear velocity (VCL), straight linear velocity (VSL), average pathway velocity (VAP), linearity (LIN), straightness (STR), wobble (WOB), hyperactivity (H), lateral head amplitude (ALH) and beat cross frequency (BCF). The data were analyzed by using independent simple t-test (IBM SPSS statistics 24). The results showed a hyperactive spermatozoa when analyzed by using leja was at 7.3%, higher than assessed with Microscope slide (2.8%). Meanwhile, other motility parameters (motility, progressive motility, VCL, VSL, VAP, LIN, STR, WOB, ALH and BCF) did not show any difference. Microscope slides can be used as a means of supporting sperms motility assesment by using CASA and more efficient.